Perlindungan Hukum Pemegang Polis Asuransi Jiwa Terhadap Penetapan Klausula Baku - Selvi Harvia Santri; Rahdiansyah Rahdiansyah (UIR Law Review, 2020)
The agreement that occurred between the insurance company and the insured was outlined in the policy. The insurance policy is standard or standard, meaning that the policy has been issued in advance by the insurance company. According to the provisions of the policy or form of insurance agreement with any name, the following attachments may not contain different words or interpretations, but in reality the policies issued by insurance companies contain languages ​​that contain different interpretations by the parties resulting in the rejection of the claims submitted by the insured or the holder policy. The issues raised in this paper are how is the standard contract arrangements for life insurance policies in Indonesia and how is the form of legal protection of policy holders for the application of life insurance policy standard clauses in Indonesia? The research method used is empirical juridical by conducting field observations through interviews to the parties later Interview results are analyzed in accordance with insurance regulations in Indonesia. The purpose of this paper is to find out the rules governing standard life insurance contracts in Indonesia and to find out the form of legal protection for policy holders against the application of a standard life insurance policy clause in Indonesia. Standard contract arrangements in Indonesia are regulated based on OJK Financial Services Authority Regulation No. 1 / POJK.07 / 2013 and Law No. 8 of 1999 concerning consumer protection and Government Regulation No. 73 of 1992 Article (19), and Law No. 40 of 2014 concerning Insurance Business, while the form of legal protection of policyholders in applying standard contracts to life insurance policy is an insurance company responsible for providing compensation if a claim is claimed by the insured, which has fulfilled the provisions in the life insurance policy, if it raises a dispute the insured is entitled to settle a dispute through a mediation institution based on Article 54 CHAPTER XI of Law number 40 concerning Insurance namely regarding the legal protection of policyholders, for the insured and insurance companies.